2002
DOI: 10.1021/bi020211b
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule Stabilizing Agent Laulimalide Does Not Bind in the Taxoid Site, Kills Cells Resistant to Paclitaxel and Epothilones, and May Not Require Its Epoxide Moiety for Activity

Abstract: Laulimalide is a cytotoxic natural product that stabilizes microtubules. The compound enhances tubulin assembly, and laulimalide is quantitatively comparable to paclitaxel in its effects on the reaction. Laulimalide is also active in P-glycoprotein overexpressing cells, while isolaulimalide, a congener without the drug's epoxide moiety, was reported to have negligible cytotoxic and biochemical activity [Mooberry et al. (1999) Cancer Res. 59, 653-660]. We report here that laulimalide binds at a site on tubulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
263
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(284 citation statements)
references
References 17 publications
21
263
0
Order By: Relevance
“…The compounds whose activity has been confirmed can be divided into two different groups, those that bind to the paclitaxel site (paclitaxel and its analogs, epothilones, eleuterobins, sarcodyctins, discodermolide, 3,17-diacetoxy2ethoxy-6oxo-B-homo-estra-1,3,5 (10)-triene) (49, 50, 56 -58), and those that share the laulimalide site (laulimalide and peloruside) (49,59).…”
Section: Discussionmentioning
confidence: 99%
“…The compounds whose activity has been confirmed can be divided into two different groups, those that bind to the paclitaxel site (paclitaxel and its analogs, epothilones, eleuterobins, sarcodyctins, discodermolide, 3,17-diacetoxy2ethoxy-6oxo-B-homo-estra-1,3,5 (10)-triene) (49, 50, 56 -58), and those that share the laulimalide site (laulimalide and peloruside) (49,59).…”
Section: Discussionmentioning
confidence: 99%
“…4 It is highly cytotoxic, inhibiting cell proliferation in numerous cancer cell lines at low nM IC 50 values. 4,5 It is also active in multidrug-resistant cancer cell lines overexpressing P-glycoprotein (P-gp) and is both effective in taxoid-resistant cell lines 5 and synergistic with taxoids. 6 These findings suggest that laulimalide may form the basis for a next-generation antimitotic agent, although we note lingering concerns over toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to identify drugs that have similar or improved pharmacological properties to paclitaxel that are also effective in paclitaxel-resistant cancer cells. Most of the microtubule-stabilizing agents have been examined for their susceptibility to MDR, and three look particularly promising because of their lack of interaction with the P-gp pump: epothilone (9 -12); discodermolide (13); and laulimalide (11,14). Recently, it was shown that laulimalide is not only more toxic than paclitaxel in cells with a MDR phenotype, but it also binds to a different site on tubulin to paclitaxel, epothilone, and discodermolide (11).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the microtubule-stabilizing agents have been examined for their susceptibility to MDR, and three look particularly promising because of their lack of interaction with the P-gp pump: epothilone (9 -12); discodermolide (13); and laulimalide (11,14). Recently, it was shown that laulimalide is not only more toxic than paclitaxel in cells with a MDR phenotype, but it also binds to a different site on tubulin to paclitaxel, epothilone, and discodermolide (11). Because laulimalide does not compete with paclitaxel for binding, it was also found to be effective in paclitaxelresistant cells that have ␤-tubulin gene mutations that modify the taxoid binding site (11), thus providing additional evidence that the laulimalide binding site is unique to that of paclitaxel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation